(untitled) (Research, Society and Development, 2022)
Head and neck radiotherapy negatively affects the dental structure of permanent teeth, causing organic and morphological changes in enamel and dentin. The aim of this study was to evaluate what changes occur in these substrates and how these changes may affect rehabilitative dental treatment. An integrative literature review was carried out, where 20 articles were selected based on the eligibility criteria proposed in the PICO strategy, using the descriptors: radiotherapy, tooth, head and neck cancer, and dental treatment, crossing them with the boolean operator AND. The databases consulted were the National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO) and Medical Literature Analysis and Retrieval System online (MEDLINE). A prevalence of experimental studies dealing with the observed changes, a systematic review, and comparisons of materials and their performance under radiotherapy were verified. According to this study, organic and morphological changes are perceptible after 30Gy, so some materials showed better performance in the face of these limitations, and may offer better adhesion, sealing, and greater longevity in rehabilitative treatments.